2019
DOI: 10.1002/fuce.201900101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Compression on the Removal of Water Droplet from GDLs of PEM Fuel Cells

Abstract: Proton-exchange membrane fuel cells (PEMFCs) with a sound potential for employing in the propulsion systems of green vehicles are currently at a high stage of development. However, appropriate water management is crucial for further development of PEMFCs. In the current investigation, the role of gas diffusion layer (GDL) compression and wettability on the removal of a water droplet from different GDLs with dissimilar levels of compression (0%, 15%, 20%, and 25%) and wettability (contact angles of 80°, 105°, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Reactant distribution, and heat and water management are critically important to the performance of PEMFCs, especially at the system level, where the proton transport from the anode to the cathode side is crucial [ 357 , 358 , 359 , 360 , 361 , 362 , 363 ]. Dynamic contact angle (DCA) is of fundamental importance in the numerical investigation to conduct material simulation of water management problems in PEMFCs [ 364 , 365 , 366 , 367 ].…”
Section: Pemfc Water Managementmentioning
confidence: 99%
“…Reactant distribution, and heat and water management are critically important to the performance of PEMFCs, especially at the system level, where the proton transport from the anode to the cathode side is crucial [ 357 , 358 , 359 , 360 , 361 , 362 , 363 ]. Dynamic contact angle (DCA) is of fundamental importance in the numerical investigation to conduct material simulation of water management problems in PEMFCs [ 364 , 365 , 366 , 367 ].…”
Section: Pemfc Water Managementmentioning
confidence: 99%
“…Experimental research methods are limited due to the high cost and difficulty in precisely observing the internal transmission process of GDL. Numerical simulation methods, such as finite element method (FEM), , lattice Boltzmann method (LBM), and pore network model, have become the main method to investigate the transport characteristics of GDL due to their low cost and flexible research scope. The water management of the GDL under compression was studied by Shi et al, and it was found that compression will increase the water saturation.…”
Section: Introductionmentioning
confidence: 99%
“…Each PEM fuel cell consists of two cathode and anode electrodes, as well as a membrane. Each electrode is constructed from at least three parts: bipolar plate accompanied by the gas channels [8,9], catalyst layer (CL) [10,11], and gas diffusion layer (GDL) [12,13]. The GDL is an important porous section of an electrode, where the reactant gases in the gas channels are passed through it and are supplied to the reaction sites at the CL.…”
Section: Introductionmentioning
confidence: 99%